2012
DOI: 10.5194/acp-12-1721-2012
|View full text |Cite
|
Sign up to set email alerts
|

Physical and optical properties of 2010 Eyjafjallajökull volcanic eruption aerosol: ground-based, Lidar and airborne measurements in France

Abstract: Abstract. During the Eyjafjallajökull eruption (14 April to 24 May 2010), the volcanic aerosol cloud was observed across Europe by several airborne in situ and ground-based remote-sensing instruments. On 18 and 19 May, layers of depolarizing particles (i.e. non-spherical particles) were detected in the free troposphere above the Puy de Dôme station, (PdD, France) with a Rayleigh-Mie LIDAR emitting at a wavelength of 355 nm, with parallel and crossed polarization channels. These layers in the free troposphere (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 50 publications
5
50
0
Order By: Relevance
“…These errors are estimated from calibrations, truncation errors for the scattering coefficient, and from noise. More details of these calculations can be found in Hervo et al (2012). The value of ω0 did not vary considerably over the measurement period in the FT, with mean values of 0.88 ± 0.02.…”
Section: Influence Of Cold Period On Aerosol Direct and Indirect Radimentioning
confidence: 98%
See 1 more Smart Citation
“…These errors are estimated from calibrations, truncation errors for the scattering coefficient, and from noise. More details of these calculations can be found in Hervo et al (2012). The value of ω0 did not vary considerably over the measurement period in the FT, with mean values of 0.88 ± 0.02.…”
Section: Influence Of Cold Period On Aerosol Direct and Indirect Radimentioning
confidence: 98%
“…The LIDAR instrument is a Raymetrics Rayleigh Mie Raman, emitting at 355 nm, with a spatial resolution of 7.5 m. More detailed descriptions of this instrument are available in Hervo et al (2012) and Freville et al (2015). The LIDAR instrument was used to determine the height of the ML using the wavelength covariance technique (Brooks, 2003).…”
Section: Optical Measurements: Nephelometer Lidar Photometermentioning
confidence: 99%
“…New significant eruptions occurred on 4-9 May and 14-19 May. The first of these events mainly influenced western Europe, from Great Britain to the Iberian Peninsula (Pappalardo et al, 2013), while the second travelled over Ireland and Great Britain and reached central Europe (Bukowiecki et al, 2011;Hervo et al, 2012). Volcanic layers were observed in the central and eastern Mediterranean area, including Greece and Turkey, in the days from 18 to 22 May Papayannis et al, 2012).…”
Section: Plume Transport Towards Northern Italy and Data Overviewmentioning
confidence: 97%
“…A 60 % volcanic contribution is reported at a high altitude station in France (Puy de Dome, 1465 m a.s.l.). According to the authors (Hervo et al, 2012), the 33 % Flexpart estimate at Puy de Dome, reported in Table 2 for the same site, would represent an underestimate, partly explained by the fact that the model does not simulate the formation of secondary aerosols. By contrast, the April episode denotes a higher degree of variability in the volcanic contributions calculated at different sites.…”
Section: Mass Contribution Of Volcanic Ash To Total Pm 10 At Cmnmentioning
confidence: 99%
See 1 more Smart Citation